2022
DOI: 10.3389/fmats.2022.893852
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Technique Approach to Enhance the Properties of Fine Recycled Aggregate Concrete

Abstract: This study investigated the properties of fine recycled aggregates (FRA), with a view to enhancing their properties for structural concrete applications. The study explored several approaches including mixing; curing; systematic screening of FRA particles below 1.18 mm to reduce the adhered cement paste (ACP) content; and the use of fly ash as 30% cement replacement to modify the microstructure of FRA concrete. To test these approaches, two series of concrete mixes were prepared at 0.45 and 0.55 w/b ratio, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Processes that include the rotor crusher or the ball mill led to reduced absorption because these techniques have a polishing effect that separates the adhered paste from the natural aggregates. Comparing the averages, it can be concluded that the jaw crusher + rotor crusher + sieving process generated FRCAs with [10,12,18,21,32,33,35,38,46,50,52,59,62] and CW [11,16,17,19,[23][24][25]36,42,43,45,47,53,57,87].…”
Section: Figure 2 Water Absorption Of Frcas From Labmentioning
confidence: 99%
See 3 more Smart Citations
“…Processes that include the rotor crusher or the ball mill led to reduced absorption because these techniques have a polishing effect that separates the adhered paste from the natural aggregates. Comparing the averages, it can be concluded that the jaw crusher + rotor crusher + sieving process generated FRCAs with [10,12,18,21,32,33,35,38,46,50,52,59,62] and CW [11,16,17,19,[23][24][25]36,42,43,45,47,53,57,87].…”
Section: Figure 2 Water Absorption Of Frcas From Labmentioning
confidence: 99%
“…Furthermore, the figures presented Fuller's Curve, which represents the grading of aggregate particles resulting in optimum packing, density, and strength of the concrete mixture [92]. [14,35,38,44,46,50,52,59,62]; (b) particle size distributions of FRCAs from CW according to recycling processes [11,16,[23][24][25]28,36,42,43,45].…”
Section: Particle Size Distribution (Psd)mentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical performance of recycled fine aggregates, supplemented with waste carbon fibers, indicated that adding waste fibers and recycled fine aggregates to concrete improves the material's characteristics [19]. Utilizing adhered cement paste elimination and fly ash treatment significantly enhanced the compressive strength and elastic modulus of recycled fine aggregates (RFA) concrete during the multi-technique approach in optimizing the properties of RFA concrete [20].…”
Section: Introductionmentioning
confidence: 99%